2014
DOI: 10.1590/s0004-28032014000200013
|View full text |Cite
|
Sign up to set email alerts
|

Lower Bifidobacteria Counts in Adult Patients With Celiac Disease on a Gluten-Free Diet

Abstract: -Context -The ingestion of gluten is responsible for the symptoms of Celiac disease, but other environmental factors can also influence. Strains of the Bifidobacterium genus have been shown to afford protection against the inflammatory response and mucosal damage caused by gliadin peptides in vitro. Objective -This study was designed to compare the concentration of fecal bifidobacteria and pH of patients with celiac disease on gluten-free diet and control subjects in order to identify if the imbalance on fecal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 31 publications
1
49
0
7
Order By: Relevance
“…The results found in this study for bifidobacteria concentration without probiotic consumption show a significantly higher bifidobacteria count in healthy subjects when compared to celiac patients, which is consistent with literature (8) . Even after probiotic consumption, the faecal bifidobacteria count in celiac patients from this study has not reached the counting in healthy individuals without probiotic consumption (Figure 3).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The results found in this study for bifidobacteria concentration without probiotic consumption show a significantly higher bifidobacteria count in healthy subjects when compared to celiac patients, which is consistent with literature (8) . Even after probiotic consumption, the faecal bifidobacteria count in celiac patients from this study has not reached the counting in healthy individuals without probiotic consumption (Figure 3).…”
supporting
confidence: 93%
“…Healthy subjects present a significantly higher concentration of bifidobacteria when compared to celiac patients, while faecal pH seems to remain the same in both situations (8) .…”
Section: Introductionmentioning
confidence: 92%
“…Patients with NCG/WS also improve symptomatically on a GFD, but it is unknown whether these patients could tolerate less restrictive avoidance or could be successfully treated with other therapies. Since patients with active CeD and nonresponders to a GFD have been found to harbor dysbiotic intestinal communities (5,(17)(18)(19), probiotics have been proposed as potential candidates to restore gut microbial homeostasis. Smecuol et al found that administration of the Bifidobacterium probiotic Natren Life Start (NLS) attenuated symptoms in CeD patients on a gluten-containing diet (20), and administration of NLS was shown to modulate innate immunity in a follow-up study (3).…”
Section: Discussionmentioning
confidence: 99%
“…This disease can manifest itself at any age and present a variety of clinical features, but it often does so in early childhood, with small intestinal villous atrophy and signs of malabsorption (Schuppan 2000;Fasano and Catassi 2001;Vivas et al 2008). Factors other than gluten, such as imbalances in the intestinal microbiota, have been associated with CD (Nadal et al 2007;Collado et al 2009;Di Cagno et al 2011;Nistal et al 2012a;Golfetto et al 2014;Elson and Alexander 2015). Forsberg et al (2004) showed a rod-shaped bacterium attached to the small-intestinal epithelium of some untreated CD patients but not to the epithelium of healthy controls, suggesting that bacteria could be involved in the pathogenesis of CD (Forsberg et al 2004;Sollid and Gray 2004).…”
Section: Introductionmentioning
confidence: 99%